2009
DOI: 10.1021/ef901031h
|View full text |Cite
|
Sign up to set email alerts
|

Polycardanol or Sulfonated Polystyrene as Flocculants for Asphaltene Dispersions

Abstract: Polycardanol with different molar mass and sulfonated polystyrene with various degrees of sulfonation were prepared by cationic polymerization of cardanol and sulfonation of polystyrene in ethyl sulfate solution, respectively. The molar masses, solution behavior, and effect of these polymers on the stability of asphaltene dispersion were studied as a function of the concentration. The results indicate that, at low concentrations, both sets of polymers behave as flocculants and dispersants at higher concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 16 publications
(25 reference statements)
4
66
0
Order By: Relevance
“…It was suggested that the most suitable polymers for asphaltene flocculation contain polar groups that can associate with asphaltenes. It was reported that polystyrene without polar groups did not modify asphaltene behavior in dilute solutions [17]. This result appears to be different from the anticipated behavior for the impact of a non-adsorbing polymer (polystyrene) in a good solvent (toluene) [18,19] on concentrated sterically stabilized colloidal particles (asphaltenes) [14].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…It was suggested that the most suitable polymers for asphaltene flocculation contain polar groups that can associate with asphaltenes. It was reported that polystyrene without polar groups did not modify asphaltene behavior in dilute solutions [17]. This result appears to be different from the anticipated behavior for the impact of a non-adsorbing polymer (polystyrene) in a good solvent (toluene) [18,19] on concentrated sterically stabilized colloidal particles (asphaltenes) [14].…”
Section: Introductionmentioning
confidence: 80%
“…For a tie line passing through point P with slope n and length l, the colloid volume fraction in the coexisting phases can be estimated using Eqs. (7), (16) and (17). Three values can be obtained for the colloid volume fraction at the binodal points Á I(x=p,q,r) , Á II(x=p,q,r) .…”
Section: Experimental Estimation Of Phase Compositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-adsorbing polymer addition to colloidal solutions can cause phase separation by depletion flocculation [1][2][3] . This mechanism leads to the formation of a polymer-rich and colloid-depleted phase (colloid gas) and a colloid-rich and polymer-depleted phase (colloid liquid) because in the absence of adsorption, a polymer free volume, known as an excluded volume, develops in the fluid adjacent to particle surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Due to its chemical similarity with nonylphenol (a synthetic chemical additive with proven action as an asphaltene stabilizer), 5 cardanol has been tested for its ability to stabilize asphaltenes in crude oil, both in its original form and after undergoing step-growth or chain-growth polymerization, demonstrating good performance compared to nonylphenol. 4,[6][7][8] Therefore, the substitution of nonylphenol by cardanol can have both environmental and economic advantages because cardanol is obtained from a renewable source and is cheaper to produce.…”
Section: Introductionmentioning
confidence: 99%